2016
DOI: 10.1016/j.atherosclerosis.2015.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive enzymes and blood flow responses to passive and active exercise in peripheral arterial disease

Abstract: Background: Peripheral arterial disease (PAD) is characterised by impaired leg blood flow, which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…As illustrated in Figure 1 and further described in Table 1, lower limb vascular function assessed by the resistance artery tests RH, PLM, and ROV exhibits strong relationships with each other (r = 0.54-0.83, p < .05), supporting the notion that they reflect some of the same physiological processes (Limberg et al, 2020). This comes in agreement with data from Rossman, Groot, Garten, Witman, & Richardson (2016) and Walker et al (2016) who observed significant correlations between PLM-induced hyperemia and RH in various populations. However, as was the case for Rossman et al (2016), vascular function assessed by FMD of the superficial femoral artery was not related to the other measurements of vascular function (e.g., PLM-induced hyperemia) examined in the current study ( Figure 1, Table 1).…”
Section: Are the Various Indices Of Vascular Function Interchangablsupporting
confidence: 85%
“…As illustrated in Figure 1 and further described in Table 1, lower limb vascular function assessed by the resistance artery tests RH, PLM, and ROV exhibits strong relationships with each other (r = 0.54-0.83, p < .05), supporting the notion that they reflect some of the same physiological processes (Limberg et al, 2020). This comes in agreement with data from Rossman, Groot, Garten, Witman, & Richardson (2016) and Walker et al (2016) who observed significant correlations between PLM-induced hyperemia and RH in various populations. However, as was the case for Rossman et al (2016), vascular function assessed by FMD of the superficial femoral artery was not related to the other measurements of vascular function (e.g., PLM-induced hyperemia) examined in the current study ( Figure 1, Table 1).…”
Section: Are the Various Indices Of Vascular Function Interchangablsupporting
confidence: 85%
“…Although it is becoming increasingly apparent that the vasculature is a significant source of free radicals (e.g. NADPH oxidase; Berry et al., ; Pipinos, Judge et al., ; Walker et al., ), many have proposed that damaged skeletal muscle mitochondria may be the primary source of ROS in PAD (Pipinos, Judge et al., ; Pipinos et al., ; Pipinos, Swanson et al., ). As mitochondrial dysfunction may limit muscle function and lead to loss of muscle mass in patients with PAD, understanding the pathophysiological consequences of inflammation, mitochondria‐derived ROS production and oxidative stress is clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…On a separate day, VL biopsies were taken from the 14 IC patients and the 10 control participants by a medical practitioner using a Bergstroem needle with suction (26,51). All biopsies were taken from the participants at rest within a 6-wk period.…”
Section: Methodsmentioning
confidence: 99%